Influência das características da água bruta no desaguamento de resíduos gerados no tratamento de água pela filtração em tubo geotêxtil - Queiroz, Sérgio Carlos Bernardo (Universidade de Ribeirão Preto, 2019)
Among the technologies available to perform the dewatering of drinking water sludge (DWS), geotextile tube filtration became a viable option, being used in several water treatment plant (WTP) in Brazil. However, some doubts about certain factors of this technology have not been fully addressed in the literature, such as: the effect that changes in raw water quality of WTP have on the dewatering characteristics of DWS; the influence of the initial solids concentration on the DWS and how the conditions of the chemical conditioning interfere in the performance efficiency of the filtration in geotextile tube. Thus the present work, through tests of bench in pressurized filter of geotextile, sought to answer such questions. The dewatering tests were carried out with three types of DWS generated on pilot scale from raw water sources with different characteristics: the type I DWS, prepared with suspension of kaolinite clay; the DWS type II, with a high turbidity, and DWS type III, with natural dissolved organic matter (NOM). The results of the dewatering tests showed that the crude water type had a direct effect on the dewatering efficiency of the residue in the geotextile, with RETA type III (predominance of NOM) resulting in a solids content after dewatering of 6%, and the type DWS I (with inorganic characteristics) achieved higher solids content, about 37%. The retention capacity of solids by the geotextile tube in the type I and type II DWS was influenced by the initial concentration of solids of the residue, where at low concentration (5 g/L of TSS), turbidity was obtained in the filtered effluent higher than 100 uT, and conversely, with a higher concentration (20 g/L TSS), the turbidity was close to 5 uT.